Nation et altérité : l’Argentine aux Expositions universelles de 1867,1878 et 1889 à Paris - Volker Barth (Les Cahiers ALHIM)
The article deals with the representation of Argentina at three Parisian universal exhibitions (1867, 1878, 1889). The years between 1860 and 1890, however, saw the progressive elaboration of a collective identity in Argentina. Not only were the fundamental state institution founded but, through very controversial discussions and constant interaction with France as the preponderant cultural reference, a system of cultural values was established. Thus the text is concerned with the modalities, the intentions and the consequences of these three displays abroad and the corresponding political debates back home. The European countries and more than the others France, the rural population and especially the gaucho, but as well, on a smaller scale, the indigenous population served the different political parties soon as examples to follow, soon as negative contrast for the establishment of a set of specifically Argentinean cultural values. Thus, the article analyses how a national identity was constructed by demarcation from constantly evolving forms of alterity.